Exchange Restrictions and Devaluation Crises - Agenor, Pierre-Richard (IMF Working Papers; Working Paper ;, 1990)
This paper develops a model of devaluation crises for an economy where foreign exchange restrictions lead to the emergence of a parallel market. The devaluation rule relates the size of the parity change to the spread between the official and parallel exchange rates. The mechanism that triggers the devaluation relates credit policy and the inflation tax. A credit expansion leads to an increase in the spread and possibly to a fall in inflation tax revenue, as agents switch away from domestic currency holdings. A devaluation reverses temporarily the process of erosion of the tax base if the associated fall in the premium raises the credibility of the new parity.